Retrospective evaluation of the utility of two-step surgery for facial basal cell carcinoma and squamous cell carcinoma - Iino, Shiro; Baba, Natsuki; Hasegawa, Takumi; Kasamatsu, Hiroshi; Oyama, Noritaka; Tokunaga, Takahiro; Hasegawa, Minoru (Frontiers in Surgery, 2022)
In older patients with facial basal cell carcinoma (BCC) or squamous cell carcinoma (SCC), surgery should be aimed to reduce treatment-related sequelae and the surgical burden with achieving local tumor care. Therefore, we adopted a two-step surgery (TSS) involving the application of a dermal regeneration template onto a skin defect after tumor resection and subsequent reconstruction by full-thickness skin grafting. We performed a detailed comparison of conventional one-step surgery (OSS) and TSS, including evaluation of local curability, postoperative sequelae (POS), and the physical burden of surgery. Forty-six patients who underwent TSS and 104 patients treated with OSS were retrospectively investigated. The cohort consisted of 77 men and 73 women (median age, 83 years). The BCC:SCC ratio was 56.7%:46.3%. The tumor size and excision margin were significantly larger in the TSS group than in the OSS group (P=0.03). Histopathological margin was positive after the first surgery in six cases, but was negative after additional resection in all cases using TSS. Local recurrence was not observed in this study. The frequency of POS was lower after TSS, but the difference was not statistically significant (17.4% vs. 27.9%, P=0.16). A shorter average operation time per session was significantly associated with the location of the vertical defect (below adipose tissue vs. within adipose tissue, estimate: -0.28 [hour], P<0.001) and surgical procedure (OSS vs. TSS, estimate: -0.13 [hour], P=0.03) by multiple regression models. The ratio of general anesthesia was lower in TSS, although the difference was not significant (9.8% vs. 17.3%, P＝0.12). Thus, TSS, similar to OSS, showed good local curability, but the TSS group had significantly larger tumors than that of OSS group in this study, it may be possible for us to reduce the surgical margin more in the future. And, despite TSS needed simple technique, POS was equal to OSS including more complicated reconstruction methods such as flaps. In addition, TSS could reduce the surgical burden in some aspects by shortening each operation time, without any adverse events during the two surgeries. TSS can be an outstanding option for facial BCC and SCC.